BDNF +/− Mice Exhibit Deficits in Oligodendrocyte Lineage Cells of the Basal Forebrain - VonDran, Melissa W. (2010)
Previous work indicated that BDNF, through the trkB receptor, increases DNA synthesis in oligodendrocyte progenitor cells (OPCs) and differentiation of post-mitotic oligodendrocytes (OLGs) of the basal forebrain (BF). In the present studies, BDNF knockout animals were used to investigate BDNF’s effects on OLG lineage cells (OLCs) in vivo. OLCs of the BF were found to express the trkB receptor, suggesting they are responsive to BDNF. Immunohistochemistry using NG2 and CC1 antibodies was utilized to examine numbers of NG2+ OPCs and CC1+ post-mitotic BF OLGs. In the embryo (E17), BDNF −/− animals display reduced NG2+ cells. This reduction was also observed in BDNF +/− mice at E17 and at postnatal day 1 (P1), P14 and adult, suggesting that BDNF plays a role in OPC development. BDNF +/− mice do not exhibit deficits in numbers of CC1+ OLGs. However, myelin basic protein (MBP), myelin associated glycoprotein (MAG), and proteolipid protein (PLP) are reduced in BDNF +/− mice, suggesting that BDNF plays a role in differentiation. These data indicate that progenitor cells and myelin proteins may be affected in vivo by a decrease in BDNF.